2001
DOI: 10.1054/bjoc.2000.1594
|View full text |Cite
|
Sign up to set email alerts
|

The level of manganese superoxide dismutase content is an independent prognostic factor for glioblastoma. Biological mechanisms and clinical implications

Abstract: SummaryWe address the issue of the role of manganese superoxide dismutase in tumorigenesis by studying a relatively homogeneous group of tumours for the correlation between amount of this anti-oxidant enzyme and prognosis. The clinical outcome of 30 patients affected by glioblastomas whose manganese superoxide dismutase content had been established at the time of first diagnosis is compared. When the survival of patients is stratified according to manganese superoxide dismutase level in the tumour, a link of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…Two enzymes involved in nitric oxide generation were selectively expressed in FHA, whereas U87MG cells showed high expression levels of mitochondrial superoxide dismutase (Mn-SOD) and glutathione transferase. Interestingly, Mn-SOD has recently been characterized as an independent prognostic factor for glioblastomas, with high tumor expression levels associated with short median survival (Ria et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Two enzymes involved in nitric oxide generation were selectively expressed in FHA, whereas U87MG cells showed high expression levels of mitochondrial superoxide dismutase (Mn-SOD) and glutathione transferase. Interestingly, Mn-SOD has recently been characterized as an independent prognostic factor for glioblastomas, with high tumor expression levels associated with short median survival (Ria et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, MnSOD was found to be associated with loss of differentiation and increased clinical malignancy in neuroepithelial origined brain tumors (Landriscina, et al, 1996;Ria, et al, 2001). MnSOD was found significantly positive in Grade IV astrocytomas and medulloblastomas and negative in normal brain samples (Cobbs, et al, 1996).…”
Section: Antioxidant Status Of the Brainmentioning
confidence: 99%
“…MnSOD may also function as a tumor suppressor; for example, it may reduce growth of tumors associated with melanoma (2), pancreatic adenocarcinoma (3,4), colorectal cancer (5), ovarian cancer (6), breast cancer (7), and multiple myeloma (8). Conversely, MnSOD may promote tumor progression in cancers, such as fibrosarcoma (9), gastric cancer (10,11), glioblastoma (12), T-cell lymphoma (13), breast cancer (14,15), cervical cancer (16), prostate cancer (17), and lung cancer (18). Therefore, the precise role of MnSOD in tumorigenesis remains elusive.…”
Section: Introductionmentioning
confidence: 99%